CONTENT OF MACRO-ELEMENTS AND ACTIVITY OF BLOOD ENZYMES IN SOWS OF DIFFERENT PREGNANCIES - Zamaziy, A.; Simon, V.; Karpenko, Y.; Bohoslovska, A. (Scientific Progress & Innovations, 2021)
The article presents the study results of macro-element nutrition of sows, the dynamics of their content and activity of enzymes in the blood, which were determined on Konelab 30 automatic analyzer, during the first, second and third pregnancies, which indicated macro-elements’ lower level in the animals’ blood dur-ing the first period of gestation. The results of the studies prove that sows of the first pregnancy use calcium intensively. Subsequently, in sows of the experimental group, the calcium content was consistently reduced to the 100th day of gestation by 1.09 times. Similar dynamics was detected by us as to the content of phosphorus in animals’ blood of the control and experimental groups (decrease by 1.08 times). However, the ratio of calcium to phosphorus was, on average, at the level of 1.18 in animals of the control group and 1.19 in sows of the experimental group. The content of potassium in the blood of sows of the control group (the first preg-nancy) increased by 1.20 times (p<0.01), while in the body of pregnant sows its intensive using was regis-tered, as evidenced by a decrease in its content by 6.06 % during pregnancy. Sodium content in the blood of sows of the control group fluctuated at the level of 164.12±2.02 – 165.06±2.36 mmol/l during the experi-ment. Calcium in the blood of animals of the first group was found, on average, 1.71±0.22 mmol/l, which was 2.14 % less than in the control, and phosphorus, on the average, in animals of this group during the ex-periment was by 1.18 times less than this indicator in the blood of sows of the third experimental group (p<0.01). The ratio of calcium to phosphorus content was higher in animals of the first experimental group and made, on average, 1.42 during the experiment, and in sows of the third experimental group it decreased to 1.23.The activity of LF was higher in the blood of animals of the second experimental group by 1.03–1.09 times, as compared with sows of the first and third experimental groups, and the activity of AST and SPGT were lower in the blood of animals of the third experimental group. The studies have shown that during the gestation period, regardless of the animals’ age, there is a decrease in the content of essential macro-elements and increase of the enzymes’ activity in the blood, which indicates metabolic stress during preg-nancy in sows’ organism.